Adipokines Mediate Inflammation and Insulin Resistance - Pessin, Jeffrey E.; Kwon, Hyokjoon (Frontiers in Endocrinology, 2013)
For many years, adipose tissue was considered as an inert energy storage organ that accumulates and stores triacylglycerols during energy excess and releases fatty acids in times of systemic energy need. However, over the last two decades adipose tissue depots have been established as highly active endocrine and metabolically important organs that modulate energy expenditure and glucose homeostasis. In rodents, brown adipose tissue plays an essential role in non-shivering thermogenesis and in energy dissipation that can serve to protect against diet-induced obesity. White adipose tissue collectively referred too as either subcutaneous or visceral adipose tissue is responsible for the secretion of an array of signaling molecules, termed adipokines. These adipokines function as classic circulating hormones to communicate with other organs including brain, liver, muscle, the immune system and adipose tissue itself. The dysregulation of adipokines has been implicated in obesity, type 2 diabetes and cardiovascular disease. Recently, inflammatory responses in adipose tissue have been shown as a major mechanism to induce peripheral tissue insulin resistance. Although leptin and adiponectin regulate feeding behavior and energy expenditure, these adipokines are also involved in the regulation of inflammatory responses. Adipose tissue secrete various pro- and anti-inflammatory adipokines to modulate inflammation and insulin resistance. In obese humans and rodent models, the expression of pro-inflammatory adipokines is enhanced to induce insulin resistance. Collectively, these findings have suggested that obesity-induced insulin resistance may result, at least in part, from an imbalance in the expression of pro- and anti-inflammatory adipokines. Thus we will review the recent progress regarding the physiological and molecular functions of adipokines in the obesity-induced inflammation and insulin resistance with perspectives on future directions.